From Suppliers to Complementors: Motivational Factors for Joining Industrial Internet of Things Platform Ecosystems - Marheine, Christian; Pauli, Tobias; Marx, Emanuel; Back, Andrea; Matzner, Martin (Proceedings of the 54th Hawaii International Conference on System Sciences (HICSS), 2021)
Spurred by the internet of things, industry firms are increasingly establishing platforms that animate an ecosystem of external actors to provide complementary offerings. But why do independent firms decide to join these ecosystems and to become complementors? The goal of this study is to disentangle their motivational factors in the context of the industrial internet of things. A theoretical framework is developed a priori based on the knowledge-based view of the firm and complementary logics. The framework is empirically explored using a case study design. Our results indicate that financial, technology, and knowledge gains positively influence the decision of complementors to join the ecosystem. Yet, our interviews reveal relative differences in motivations based on complementors’ uncertainty. Our findings contribute to the research on joining nascent digital platform ecosystems from a complementor perspective and the growing stream of research on industrial internet of things platform
Keywords: Industrial Internet of Things; Platform; Ecosystem